65,000 South Asian farmers’ resilience and income sustained through drought-tolerant maize - CGIAR Research Program on Maize (2021)
The Heat Tolerant Maize for Asia (HTMA) project develops and disseminates heat-tolerant hybrids in 5 South Asian countries. Through a licensing model to small and medium-size seed companies, the first hybrids were released in the project's 3rd year, benefiting ca. 65,000 farmers in 4 HTMA countries with higher yields and income. Growing heat-tolerant, high-yielding maize can form part of farmers' climate change adaptation response (5, 6), which is better supported institutionally in South Asia than in East Africa (4).